Effect of proprioception training on Pain and knee joint position sense of athletes with Genuvalgum - Mohammad Rahim Amiri; Masoud Golpayegani; Fariba Moradi Vastgani; Mohammad Mirghasemi (Biyumikānīk-i varzishī)
Objective: The purpose of this study, the effect of strengthening exercises on proprioception athletes with knee joint position sense in Genuvalgum. Methods: A total of 30 athletes with an age range between 20-30 years voluntarily participated in this study and were randomly divided into two groups (experimental and control) groups. Proprioceptive training program for experimental group for 8 weeks (3 sessions per week, 3 times daily, 20 minutes). The pre-test and post-test to detect the joint position (PFPPS) and the knee proprioception were measured via digital pictures using Auto-CAD software. Data analysis software SPSS V. 16 using paired t-test and one-way analysis of variance. Results Knee joint proprioception exercises can reduce the reconstruction error. Conclusion: These exercises improve proprioception in athletes with Genuvalgum.